FEATURES OF ENGLISH OAK CROWN DEVELOPMENT AND REPRODUCTION IN SEED ORCHARDS AT THE HUTYANSKE FORESTRY ENTERPRISE, KHARKIV REGION - Los, S. A.; Godovany, O. M.; Grygoryeva, V. G.; Gubin, Ye. A. (Forestry and Forest Melioration, 2018)
Introduction Clonal seed orchards (CSO), which provide forestry with improved or elite seeds, now are the most important objects of the forest-seed establishment in many countries worldwide. The study of the clones growing at CSOs and clonal archives give an opportunity to evaluate the plus trees by the intensity of growth. The investigation of families grown at the seedling seed orchards (SSO) allows estimating the growth rate of plus tree progenies. In addition, such studies allow providing practical guidance on the effective distance between trees at the CSO and SSO. The aim of this work was to compare of the crown development, the health and reproduction intensity of English oak (Quercus robur L.) clones at the CSO and families at the SSO at the age of 19 and 20 respectively in Hutyanske Forestry Enterprise, Kharkiv region. Materials and Methods The study was carried out at seedling and clonal seed orchards of English oak in in Hutyanske Forestry Enterprise, Kharkiv region. The SSO was established in 1999, with 6 ? 6 m placement of planting sites. There are the progenies of 27 clones of plus trees, selected in the Kharkiv, Sumy and Donetsk regions, at the SSO. The CSO was established in 2001 with placement of plants of 8 ? 8 m. There are 102 grafts of 31 clones, among which 22 are the best trees, selected in Volodymyrivske and Parkhomivske forestries of Hutyanske Forestry Enterprise in 2000, and 19 are clones of plus trees, selected in the Kharkiv, Sumy and Donetsk regions at the clonal orchard. During observation, the tree height, the crown projection diameter, the health condition, the available reproduction, defects and damages for each tree were determined and the crown volumes were calculated at the SSO and CSO. To evaluate and compare the families and clones their point complex assessment was carried out by the crown development and the reproduction condition and intensity (ovary formation). The data were compared with the mean values at the seed orchard. Results At the SSO, the trees’ vitality was 90 %. Indices of the crown volume of different families ranged from 187.6 m3 to 560.1 m3 and were 349.9 m3 on average. Only two families significantly exceeded the SSO average by crown volume. Fourteen families from 27 have the value above the average. For 13 families the volume was below the average. The trees’ health condition was mostly good at the SSO. The average number of the ovary formation intensity was 1.4 points. According to the results of the complex evaluation, none of the families scored more than 11 points. Most families were included into the group of relatively prospective ones, and only 5 of them (Tr-15, P-20, D-5, P-21, and L-7) were assigned to the non-prospective ones. Plant vitality was somewhat lower at the CSO as compared to that at the SSO and amounted to 84.6. The crown volume of clones ranged from 85, 1 m3 to 605.0 m3 and was 391.2 m3 on average. In general, the crown volume of 11 clones was below the average plantation value, by 35.7% on average. Nineteen clones exceeded the average rate by 20.7% on average. Among them, 10 clones exceeded the average value by more than 20 % and 8 clones had more than 20 % lower crown volume. The intensity of the ovary formation at CSO was generally better than at SSO (average number was 2.0). The average indexes for the three families were less than 1 while the reproduction of 16 families was estimated by 2 or more point. The rest 9 families were in the medium range. As a result of the complex analysis of clones at CSO, more notable differences were found between clones than between families. According to the results of the study, a group of five perspective clones (L-5, D-3, Тr-2, Ph-10, Ph-2, and Vl-5) was selected which scored above 11 points. And only 8 clones were assessed to a group of non-prospective ones. Most families were included in the group of relatively prospective ones. In almost all cases, the height of the trees was greater and the diameter of the crown projection was lower at the SSO compared to the CSO. At the same time, the crown volume, which characterizes its development as a whole, in the majority of cases was higher at the CSO. A slightly higher variability of the clone crown volume at CSO was detected as compared to SSO: variation coefficients were 32.8% and 26.0%, respectively. Conclusions The advantages of grafts in the crown development were determined both by the crown projection diameter of and by the crown volume, and of families, by height. The average crown volume ranged from 85.1 m3 (Ta-7) to 605.0 m3 (Vl-2) for trees at the clonal seed orchard and from 187.6 m3 (P-21) to 560.1 m3 (Tr-15/17) for families at the seedling seed orchard. Thinning with the removal of every second row (50 % of trees) is recommended to improve the lighting and nutrition of the trees at the SSO. The trees spacing is currently optimal at the CSO. However, it is expedient to selectively remove 30 % of trees in the future, over the next five years. The reproduction intensity was generally better at the CSO than at the SSO (the average number was 2.0 for CSO and 1.4 for SSO). According to the results of the integrated assessment, among the 31 clones at the CSO, five are promising, eight have low prospects, and the rest are relatively promising. At the SSO, 22 families from 27 have been included in the relatively promising group. 6 Figs., 3 Tables, 11 Refs.